Frequency of Slips of the Tongue and Typing in Pakistani Politicians’ Speeches and Guide Books - Riaz Hussain; Farah Zahid; Aisha Ilyas (Journal of Management Practices, Humanities and Social Sciences, 2021)
This study examines the frequency of slips of the tongue and typing in Pakistani politicians’ speeches and guidebooks. Slips of the tongue occur in formal and informal situations. In formal situations, slips of the tongue can cause serious problems such as dismissal from office or job, losing voters’ favors and even plane crashes at airports. In informal situations, slips of the tongue can cause relationship problems. Therefore, slips of the tongue have been engaging the attention of psychologists and linguists. The recorded literature, according to western scholars, shows that the earliest systematic studies were undertaken on the slips of the tongue in the 19th century. Corpora, experimental and exploratory studies have been done on slips of the tongue. In the current study, with an exploratory approach, seven Pakistani politicians’ speeches were downloaded from the social media website and analyzed for slips of the tongue. Besides, two ‘key books’ (notes books for MCQs) were analyzed for slips of typing. The data was analyzed by using insights from theoretical work of Fromkin (1973) and Mackay (1993). The findings show that “substitution” occurred more frequently than other types of slip of the tongue. Furthermore, the results also reveal that “transposition” as type of slip of typing occurred more frequently than other types. The author suggest that the next scholar perform investigation on slip tongue, which can be discovered in a variety of situations and situations, such as in a video or in everyday speech. It also advises that this issue be developed and explored further in terms of changing objects or theories.